Crisis intervention handbook : assessment, treatment, and research - Roberts, Albert R. (Belmont, Calif. : Wadsworth Pub. Co., 1990)
This book integrates theory and practice so that students, will be equipped with the practical knowledge needed to help their clients and will also be well versed in the theory that all clinicians need to know.
Includes bibliographical references and index.
Keywords: Crisis intervention (Mental health services) -- Handbooks, manuals, etc; Community mental health services -- Handbooks, manuals, etc